Perlindungan Hukum Bagi anak Sebagai Konsumen Rokok Terhadap Praktik Jual Beli Rokok Di Kecamatan Panakkukang Kota Makassar (LEGAL DIALOGICA, 2025)
This study aims to analyze legal protection for children as active smokers, specifically in the context of the ban on cigarette sales to minors in Panakkukang District, Makassar City. The widespread access of children to cigarettes from retail vendors demonstrates weak oversight and implementation of local laws, despite the fact that children are legal subjects who deserve special protection. The method used was empirical juridical with a sociological and normative approach. Data were collected through interviews, observations, and questionnaires with children who are active smokers, their parents, cigarette vendors, and Public Order Agency (Satpol PP) officers. The data were analyzed qualitatively to assess the extent to which legal norms are implemented in the field. The results indicate that legal protection for children is ineffective. Retail vendors are still free to sell cigarettes to children without considering age restrictions. Law enforcement remains weak, compounded by the permissive attitudes of some parents and a lack of socialization of legal regulations in the community. Children living in densely populated or underprivileged neighborhoods tend to have easier access to cigarettes with minimal supervision than children from more affluent families. One recommendation is the need for consistent increased supervision and law enforcement by relevant authorities. Local governments, the Public Order Agency (Satpol PP), and the police need to play an active role in controlling the distribution of cigarettes to children. Legal education for businesses and the public is also crucial to prevent violations. Furthermore, the establishment of technical regulations at the local level, such as Village or District Regulations, can be a concrete solution to strengthening legal protection for children as consumersAbstrak:Penelitian ini bertujuan untuk menganalisis perlindungan hukum bagi anak sebagai konsumen perokok aktif, khususnya dalam konteks larangan penjualan rokok kepada anak di bawah umur di Kecamatan Panakkukang, Kota Makassar. Maraknya anak-anak yang mengakses rokok dari penjual eceran menunjukkan lemahnya pengawasan dan implementasi hukum di tingkat lokal, padahal anak merupakan subjek hukum yang harus mendapatkan perlindungan khusus.Metode yang digunakan adalah yuridis empiris dengan pendekatan sosiologis dan normatif. Data dikumpulkan melalui wawancara, observasi, dan kuisioner terhadap anak-anak perokok aktif, orang tua, penjual rokok, serta aparat Satpol PP. Data dianalisis secara kualitatif untuk menilai sejauh mana norma hukum terlaksana di lapangan.Hasil penelitian menunjukkan bahwa perlindungan hukum bagi anak belum berjalan efektif. Penjual eceran masih bebas menjual rokok kepada anak tanpa mempertimbangkan batas usia. Penegakan hukum masih lemah, ditambah sikap permisif sebagian orang tua dan kurangnya sosialisasi aturan hukum di masyarakat. Anak-anak yang tinggal di lingkungan padat atau kurang mampu cenderung memiliki akses lebih mudah terhadap rokok, dengan tingkat pengawasan yang minim dibandingkan anak dari keluarga mampu. Saran yang dapat diberikan adalah perlunya peningkatan pengawasan dan penegakan hukum oleh aparat terkait secara konsisten. Pemerintah daerah, Satpol PP, dan kepolisian perlu berperan aktif dalam mengontrol peredaran rokok kepada anak. Edukasi hukum kepada pelaku usaha dan masyarakat juga penting untuk mencegah terjadinya pelanggaran. Selain itu, pembentukan regulasi teknis di tingkat lokal, seperti Peraturan Kelurahan atau Kecamatan, dapat menjadi solusi konkret dalam memperkuat perlindungan hukum anak sebagai konsumen.